In vitro susceptibility to 19 agents other than β-lactams among third-generation cephalosporin-resistant Enterobacteriaceae recovered on hospital admission. (19th January 2017) - Mischnik, A.; Baumert, P.; Hamprecht, A.; Rohde, A. M.; Peter, S.; Feihl, S.; Knobloch, J.; Gölz, H.; Kola, A.; Obermann, B.; Querbach, C.; Willmann, M.; et al.
Abstract : Objectives: As part of the multicentre Antibiotic Therapy Optimisation Study, MIC values of 19 non-β-lactam agents were determined for third-generation cephalosporin-resistant Escherichia coli, Klebsiella species and Enterobacter species (3GCREB) isolates collected in German hospitals. Methods: A total of 328 E. coli, 35 Klebsiella spp. (1 Klebsiella oxytoca and 34 Klebsiella pneumoniae ) and 16 Enterobacter spp. (1 Enterobacter aerogenes and 15 Enterobacter cloacae ) isolates were submitted to broth microdilution antimicrobial susceptibility testing with the MICRONAUT system. MICs of fluoroquinolones (levofloxacin and moxifloxacin), aminoglycosides (gentamicin, tobramycin, amikacin, streptomycin, neomycin and paromomycin), tetracyclines (tetracycline, minocycline and tigecycline), macrolides (erythromycin, clarithromycin and azithromycin) and miscellaneous agents [trimethoprim/sulfamethoxazole, chloramphenicol, nitrofurantoin, colistin and fosfomycin intravenous (iv)] were determined and reviewed against 2016 EUCAST breakpoints. Results: The MIC of levofloxacin was >2 mg/L for 128 of 328 E. coli and 8 of 35 Klebsiella spp., but only 1 of 16 Enterobacter spp. Rates of resistance to trimethoprim/sulfamethoxazole were high (>70%), except for Enterobacter spp. Rates of resistance to colistin and fosfomycin iv were still low. About 20% of the tested isolates were resistant to chloramphenicol. Only 1 (of 328) E. coli isolate had an MIC of amikacin >16 mg/L and only 33 of 328 E. coli and 1 of 35 Klebsiella spp. had an MIC of tobramycin >4 mg/L, whereas average gentamicin MICs were in general more elevated. A tigecycline MIC >2 mg/L was only found for 1 of 16 Enterobacter spp., but in none of the E. coli or Klebsiella spp. isolates. Conclusions: Our study gives insight into previously unreported non-β-lactam MIC distributions of 3GCREB isolates.